Strategi Komunikasi Publik Dalam Upaya Pencegahan Stunting Melalui Program Forum Generasi Berencana (Genre) di Provinsi Nusa Tenggara Barat - Ayudya, Devira Bunga; Hidayat, Ofi (Universitas Gajah Putih, 2025)
Stunting is a public health problem that has a long-term impact on the quality of human resources, especially in the Province of West Nusa Tenggara (NTB) which is one of the priority provinces for accelerating stunting reduction in Indonesia. This study aims to analyze the public communication strategy carried out through the Planned Generation Forum (GenRe) program in an effort to prevent stunting among adolescents. This study uses a descriptive qualitative approach, data collection is carried out using in-depth interview techniques, observation, and documentation of the administrators and facilitators of the NTB GenRe Forum. The findings in this study indicate that the NTB GenRe public communication strategy utilizes a peer-to-peer approach, nutrition education, digital campaigns, and cross-sector collaboration with the support of online and offline media. McGuire's persuasive communication model is used to analyze the effectiveness of message delivery, where internal factors (member capacity, motivation) and external factors (stakeholder support, audience characteristics) play an important role in determining the success of the program. This study emphasizes the importance of a structured and participatory communication strategy in building adolescent awareness of the issue of stunting and encouraging sustainable changes in health behavior. Stunting is a public health problem that has a long-term impact on the quality of human resources, especially in the Province of West Nusa Tenggara (NTB) which is one of the priority provinces for accelerating stunting reduction in Indonesia. This study aims to analyze the public communication strategy carried out through the Planned Generation Forum (GenRe) program in an effort to prevent stunting among adolescents. This study uses a descriptive qualitative approach, data collection is carried out using in-depth interview techniques, observation, and documentation of the administrators and facilitators of the NTB GenRe Forum. The findings in this study indicate that the NTB GenRe public communication strategy utilizes a peer-to-peer approach, nutrition education, digital campaigns, and cross-sector collaboration with the support of online and offline media. McGuire's persuasive communication model is used to analyze the effectiveness of message delivery, where internal factors (member capacity, motivation) and external factors (stakeholder support, audience characteristics) play an important role in determining the success of the program. This study emphasizes the importance of a structured and participatory communication strategy in building adolescent awareness of the issue of stunting and encouraging sustainable changes in health behavior.